BEBERAPA FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK ORANG PRIBADI ATAS PERILAKU PENGGELAPAN PAJAK - Angka Wijaya; Miftahul Jannah (Fakultas Ekonomi Universitas IBA, 2017)
This study aimed to analyze the factors that influence the perception of thetaxpayer on tax evasion behavior. As these factors is the effect of the tax system, theunderstanding of taxation, service tax authorities and tax penalties. The study populationwas on the faculty in the accounting department of private universities located in the cityof Palembang who had been in accreditation by BAN-PT rated B. The sample wasdetermined by saturation sampling method, the data collected by the distribution ofquestionnaires. The method of analysis used in this study were multiple linear regression.Based on the results of the analysis show that the tax system a significant negativeeffect on the perception of the taxpayer on the behavior of tax evasion, understanding thetax has no effect on the perception of the taxpayer on the ethics of tax evasion, theservice tax authorities had no effect on the perception of the taxpayer on the ethics of taxevasion, and tax penalties a significant negative effect on the perception of the taxpayeron tax evasion behavior. The most dominant variable affecting the perception of thetaxpayer on the ethics of tax evasion is tax penalties because it has a standard betacoeficient 0.328.